Prediction of pressure drop of slug flow in vertical pipes using mechanistic model - Mohamad Fakhrol Radzi, Zulkefli (2014)
Due to the variability of flow pattern of gas liquid two-phase flow and complexity of flow mechanism,it is very difficult to seek a single model which is able to predict pressure drop and fit for any flow condition. when the existing model of two-phase flow pressure drop is used to predict the pressure of the conditions of producing gas well,a large error occurs.Therefore, it is necessary,based on the experimental data of gas-water two phase flow,to research the flow mechanism and discover the regular existing in the process of fluid property changing .On the basis of the current two-phase flow pressure drop model, it is important to explore modified pressure loss model applicable for producing gas well with water,to improve predictability of the pressure drop of gas wells,and to provide the theory and technology guidence for development of gas reservoir with water. Underbalanced drilling (UBD) has increased in recent years because of the many advantages associated with it. These include increase in the rate of penetration and reduction of lost circulation and formation damage. Drilling of deviated and horizontal wells also increased since recovery can be improved from a horizontal or a deviated well. The drilling of deviated wells using UBD method will reduce several drilling related problems such as hole cleaning and formation damage. Prediction of flow and pressure profiles while drilling underbalanced in such wells will help in designing and planning of the well. The aim of this research is to predict the pressure drop of slug flow in the certain pressure in vertical pipes using mechanistic model and to study the behavior of the flow profile in the drillstring and the annulus under UBD conditions through the use of mechanistic two phase flow models. Mechanistic two phase flow models is been used In this research to predict the liquid hold up for phase gas- liquid slug flow which is important for the accurate calculations of the pressure drop.In particular, its evaluation is important for the vertical pipes since the liquid hold up in the slug body is the main contributor to the hydrostatic pressure drop which quite significant for the verticals flows. Further development of mechanistic models has allowed accurate prediction of wellbore pressure. Many Underbalanced Drilling operations require the use of nitrified diesel as the drilling fluid.Thus two phase flow will exist both in the drill pipe and the annulus